2013
DOI: 10.2478/pjvs-2013-0038
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effect of silybin against lasalocid-induced toxicity in HepG2 cells

Abstract: Lasalocid is an ionophore coccidiostatic agent frequently used in poultry. Its extensive use causes the formation of residues in edible tissues and eggs which may pose a risk to consumers. Silybin is the main compound extracted from the herb milk thistle Silybum marianum and its hepatoprotective effect has been reported in literature.The aim of the study was to compare lasalocid and silybin cytotoxic effects followed by their combined use in HepG2 cell line. A cytoprotective effect resulting from the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Monensin, narasin and salinomycin demonstrated high IC 50 values across all the mammalian cells tested with the exception of human fibroblasts and monensin also produced no erythrocyte lysis at concentrations ≤128 μg/ml after a 1‐hr exposure. Cytotoxicity testing results suggest that of the four ionophores tested, lasalocid had the lowest IC50 values and this was consistent with the observations of other studies conducted using HepG2 cells (Cybulski, Radko, & Rzeski, ; Radko, Cybulski, & Rzeski, ). In our previous work, lasalocid formulated as an intramammary suspension was successfully able to treat experimentally‐induced S. uberis mastitis in lactating dairy cows without causing any untoward negative effects (Wang et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Monensin, narasin and salinomycin demonstrated high IC 50 values across all the mammalian cells tested with the exception of human fibroblasts and monensin also produced no erythrocyte lysis at concentrations ≤128 μg/ml after a 1‐hr exposure. Cytotoxicity testing results suggest that of the four ionophores tested, lasalocid had the lowest IC50 values and this was consistent with the observations of other studies conducted using HepG2 cells (Cybulski, Radko, & Rzeski, ; Radko, Cybulski, & Rzeski, ). In our previous work, lasalocid formulated as an intramammary suspension was successfully able to treat experimentally‐induced S. uberis mastitis in lactating dairy cows without causing any untoward negative effects (Wang et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…The results both from primary cells and cell lines assays proved that lasalocid causes a chain of cellular damages, which lead to the death of cells [8, 27–29]. The studies on FaO and HepG2 cell lines showed clearly that lasalocid toxicity targeted cell metabolism [29, 30]. The EC 50 of lasalocid MTT assay was found in range 4.0–9.0  μ M on rat (FaO) and human (HepG2) cell lines, which corresponds with EC50 for chicken cell lines (LMH).…”
Section: Discussionmentioning
confidence: 99%
“…The data of our previous studies have been shown an antagonistic interaction between lasalocid and silybin on rat (FaO) and human (HepG2) hepatoma cell lines. As a result of silybin interference a significant decrease of lasalocid cytotoxicity was revealed in both cell cultures [29, 30]. Hepatocellular injury due to high level of lasalocid seems to be the primary event.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that lasalocid induces cytotoxic effects in liver cells by disturbing membrane ion transport and mitochondrial injury. Silybin exerts cytoprotective effects on HepG2 cells against the cytotoxic effects of lasalocid. , Zidovudine (AZT) is a nucleoside analogue that is commonly used to help control HIV infection. Moreover, it is also used with the antitubercular drug isoniazid (INH) due to the susceptibility of AIDS patients to tuberculosis.…”
Section: Detoxification Effectsmentioning
confidence: 99%